Korelasi Sikap Narima Ing Pandhum dengan Subjective Well-Being Driver Gojek di Daerah Kemiri Salatiga - Nova Sangwana Putra; Berta Esti Ari Prasetya (Universitas Kristen Maranatha, 2021)
This study aims to determine the correlation between Narima Ing Pandhum's attitude and Subjective Well-Being on Gojek drivers in the Kemiri area of Salatiga. Narima Ing Pandhum's attitude is an attitude of self-acceptance in the past, present and future while Subjective Well-Being is an evaluation of oneself based on life experiences. This study uses a quantitative method of correlational test. The measuring instrument used is the Subjective Well-Being scale = 0.8 and the Narima Ing Pandhum scale = 0.89 with the participants in this study totaling 44 Gojek drivers. Based on the results of the correlational test, it shows that there is an insignificant negative correlation between the attitude of narima ing pandhum and subjective well-being with a value of r = -0.195 (p>0.05). Keywords: subjective well-being, narima ing pandhum, driver Gojek